The Application of Life Skills in Making of Alum from Can Waste (Proceedings of the International Conference on Education, 2019)
Life skills learning is one of the learning processes where students learn various conceptsand apply them in daily life. In the process of learning, students are faced with certain situations sothat they get a new learning experience perceived benefits. The objective of this research was: 1) toknow the mastery of academic and social life skills in practice of making alum from waste can, 2) toknow the motivation of students in the implementation of the practice of making alum from wastecan, 3) know the concept mastery aspect in the implementation of the practice of making alum ofwaste can. This research is a quasi-experiment with one-group posttest study design. Researchsubjects were students of Chemistry Education Department who take inorganic chemistryexperiment. Instruments used were observation sheet and rubric indicator of work assessment (foracademic and social life skill) and questionnaire (for motivation), and subjective test: pre-test andpost-test (for conceptualization). The research data was analyzed by qualitative descriptive analysistechnique, that is by calculating the average of every aspect that is assessed and converting it intoqualitative criteria. Based on the result of research indicated that student's motivation in practice getsgood category while the value of mastery of academic skill and social life skill was in good categoryand mastery of concept got very good category.
Keywords: life skills; inorganic chemistry experiment; motivation; alum (potassium alum)